2008
DOI: 10.1080/01639360802059712
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Testing of an Instrument to Establish Eating Profiles of Clients in Nursing Homes or Elderly Homes

Abstract: "Eating profiles" can be defined as types of clients distinguished by combinations of food preferences, consumption patterns, and preferences for ambiance. The purpose of this article is to describe the development and initial testing of an instrument to establish eating profiles of residents of nursing homes or elderly homes. We constructed a 35-item, 4-subscale questionnaire. This self-administered, usable instrument derived five eating profiles from clients' perspectives. Insight in eating profiles is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…A mealtime instrument was developed for the purpose of this study. Several of the included mealtime ambience variables are consistent with descriptions by NH residents concerning the quality of a dining experience, such as having a variety of choices, the provision of good service from friendly and knowledgeable staff, receiving help/assistance as needed and being served in an attractive environment (40)(41)(42). The interobserver reliability of the mealtime variables was acceptable (43), with a median Cronbach's alpha value of 0.73.…”
Section: Discussionsupporting
confidence: 54%
“…A mealtime instrument was developed for the purpose of this study. Several of the included mealtime ambience variables are consistent with descriptions by NH residents concerning the quality of a dining experience, such as having a variety of choices, the provision of good service from friendly and knowledgeable staff, receiving help/assistance as needed and being served in an attractive environment (40)(41)(42). The interobserver reliability of the mealtime variables was acceptable (43), with a median Cronbach's alpha value of 0.73.…”
Section: Discussionsupporting
confidence: 54%
“…The same research group also found residents appreciated opportunities to order alternatives, try new foods, return items they disliked, and bring in food from family members or other places (32). Several questionnaires have been developed in recent years to better understand residents' satisfaction with food services and their preferences (39)(40)(41). Obtaining input from residents and family through food committees is one means for promoting preferences, and menu-planning typically provides opportunity for this input.…”
Section: Mealtimes In Nursing Homesmentioning
confidence: 94%